P393 Patient and physician perspectives on the management of inflammatory bowel disease: Role of steroids in the context of biologic therapy. (15th January 2020) - Afzali, A; Armuzzi, A; Bouhnik, Y; Bressler, B; Hart, A; Rubin, D; Sans, M; Siegmund, B; Sninsky, D
Abstract: Background: Corticosteroids are a mainstay of inflammatory bowel disease (IBD) treatment but are not as effective as maintenance therapy and prolonged exposure is associated with significant morbidities. We assessed real-world management of IBD using an international online survey of patients (patients) and physicians and present results related to steroid use for IBD. Methods: The online survey was conducted in Canada, France, Germany, Italy, Spain, UK, and the USA. The mixed-recruitment methodology was used: patients were recruited by physicians, pt advocacy groups, and panels; physicians were recruited by recruitment agencies and panels. Eligible patients were adults with Crohn's disease (CD) or ulcerative colitis (UC) (targeted 1:1 ratio CD:UC) who had received IBD treatment but had not had surgery for UC. Eligible physicians were gastroenterologists who had treated ≥12 CD patients and ≥12 UC patients (≤70% with a disease of mild severity) in the prior month and were responsible for treatment decisions. Results: Surveys were completed by 2398 IBD patients (1368 CD, 1030 UC) and 654 physicians. Mean ages were 43 y and 45 y for patients with CD and UC, respectively; 60% and 55% were female. Most patients (93% CD, 78% UC) had moderate/severe IBD per clinical criteria; 71% and 47%, respectively, had ever required hospitalisation. Physicians had a mean monthly caseload of 42.9 CD patients and 43.3 UC patients, and 62.4%–67.2% of their IBD patients had moderate/severe disease. Biologic therapy was currently used by 50% of CD patients and 32% of UC patients, consistent with results for physicians (54% CD, 43% UC). Most patients (69% CD, 58% UC) reported a loss of response (LOR) to prior treatments, and most physicians reported that their patients experienced a LOR to biologic therapy fairly/very frequently (66% CD, 56% UC). Approximately 75% of IBD patients had ever used steroids for their IBD; steroid use of ≥4 or ≥6 months in the past year was reported by 35% and 18% of CD patients, respectively, and by 40% and 19% of UC patients. Physicians reported that 40% and 14% of their IBD patients used steroids for ≥4 or ≥6 months in the past year. Among patients currently receiving steroid therapy, many (48% CD, 42% UC) were concerned about any steroid use, and two-thirds reported wanting to stop steroid treatment as soon as the disease was under control. Only 27% of physicians reported a concern about any steroid use; approximately half reported a concern about ≥4 months of steroid use per year. Conclusion: This international survey demonstrated that steroid use is prevalent and LOR to biologics is common among moderate/severe IBD patients. There were differences in pt and physician perception of steroid use; many physicians believed ≥4 months of steroid use per year was not a concern. A significant unmet need remains for treatments that provide sustained control of IBD.